Interest rate policies and domestic savings mobilization: A survey of the empirical evidence of Asian countries - Uwe Corsepius; Bernhard Fischer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
The liberalization of interest rates has become more and more an integrated part of the policy advice given to developing countries in order to stimulate domestic savings and to improve the allocative efficiency of investments . One of the most critical assumptions behind this policy approach refers to a high and positive interest rate elasticity of savings. Empirically, this assumption seems not to be supported unanimously. Giovannini (1983) , for instance, concludes from his survey of a sample of econometric studies that the notion of a positive impact of higher interest rates on national savings is not warranted empirically. This would lead to the conclusion that the expected success from interest liberalization policies would be questionable. However, such a judgement is not justified because the mentioned survey has various shortcomings. First, the range of empirical studies covered in the overview is rather limited. Second, the discussion of the interest rate elasticity of savings is not differentiated enough with respect to different savings aggregates. Third, some of the specification and methodological problems existing in estimating interest elasticities of savings are not tackled sufficiently.
Keywords: 330